Coordination Failures, Clusters and Microeconomic Interventions - Andrés Rodríguez-Clare (Inter-American Development Bank, Research Department, 2005)
This paper discusses coordination failures, their relevance to developing countries, and the circumstances under which they occur, arguing that that clusters can be seen as agglomerations of firms and organizations in related economic activities among which coordination failures are likely to arise. In other words, clusters provide opportunities for microeconomic interventions that promote coordination and collective action to improve productivity. Subsequently presented is a model of a small economy plagued by sector or cluster-specific coordination failures, which demonstrates that policy should foster cooperation in sectors where the economy already shows comparative advantage. In regard to innovation, general policies that aim to increase innovation across the board are likely to be inferior to policies that take a more selective approach by trying to induce the development of innovation clusters in areas of comparative advantage. The paper concludes with suggestions on how an understanding of coordination failures and clusters can form the basis for a set of effective microeconomic interventions for middle-income countries.
Keywords: 330; Regionales Cluster; Agglomerationseffekt; Produktivität; Innovation; Koordination